Modelling and assessment of sustainable urban drainage systems in dense precarious settlements subject to flash floods - Fonseca Alves, Luma Gabriela; de Oliveira Galvão, Carlos; de Farias Santos, Bervylly Lianne; Fernandes de Oliveira, Eldson; Andrade de Moraes, Demóstenes (LHB hydroscience journal, 2022)
In developing countries, dense, precarious and informal settlements are common. In the tropics, the occurrence of intense rainfall and the increased impervious surfaces have led to disastrous flash floods. Sustainable urban drainage systems (SUDS) are an alternative to enhance stormwater management and runoff control, providing benefits related to social and environmental domains. This study aims to ground the development of procedures for SUDS implementation to mitigate flooding, and to maximize urban benefits. We present a modelling framework of SUDS implementation, using the Storm Water Management Model (SWMM) to simulate various SUDS scenarios. An application to a small catchment in Brazil considered permeable pavements, bioretention systems, infiltration trenches and rainwater harvesting systems, introduced in both public and private areas. The results demonstrate that SUDS implemented in public spaces, although they may increase access to public facilities, do not completely avoid flooding in the denser parts of the catchment. In such cases, measures must be implemented in private lots due to the reduced amount of available public spaces. Such evidence shows that one of the key elements for flash flood management in consolidated dense and precarious urban settlements is the integration of SUDS measures with the engagement of local inhabitants in decision-making.